POLA SPASIAL DAMPAK DISPERSI GAS NITROGEN DIOKSIDA KABUPATEN SERANG PROVINSI BANTEN - Putra, Ahmad Pratama (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
The main activities in Serang Regency which are suspected to produce pollutants and air emissions include industrial business activities where the pollutants produced are in the form of Nitrogen Dioxide (NO2) gas which is not only dangerous for humans and animals, but also dangerous for plant life. Therefore this study tries to examine the spatial pattern of NO2 gas dispersion and its impact on settlements in Serang Regency. Based on the results of ambient air quality measurements in Serang Regency, which have been measured by the Serang Regency Environmental Agency from 2015 - 2019 for the NO2 parameter, it is seen that none of them exceed the standard of the PP No. 41 of 1999 concerning Air Pollution Control. The results of gas dispersion modeling show a tendency that gas concentration is relatively high in industrial zones, which indicates the contribution of gases from industrial business activities in several monsoons. The most extensive settlement affected by NO2 gas with the highest value (40-50 µg / Nm3) is in Cikande District covering an area of 396.4 Ha which occurs during the west monsoon (December-February).